Erich Gutenberg und die Theorie der Unternehmung - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1998)
Ich möchte in diesem Vortrag Beziehungen zwischen Gutenbergs Theorie der Unternehmung, die in seiner Habilitationsschrift angelegt und in den Grundlagen der Betriebswirtschaftslehre entfaltet ist, und aktuellen Entwicklungen in der Theorie der Unternehmung herstellen. Obwohl der Anlaß für diesen Vortrag das Thema hinreichend rechtfertigt, stellt sich die Frage, ob mein Vorhaben ein wissenschaftlich sinnvolles Unterfangen darstellt: Kann Gutenbergs Theorie der Unternehmung noch aktuell sein? – – One might easily gain the impression that the academic work of Professor Erich Gutenberg, whose centenary provides the occasion for this lecture, is outdated and has lost touch with contemporary economic theories of the firm. However, this impression would be wrong, as this paper demonstrates with reference to the most recent research into the theory of the firm. Professor Gutenberg was the first and the most influential German researcher in his field, the theory of the business enterprise (Betriebswirtschaftslehre), to show how closely the various functions and departments of an enterprise are interdependent. Thus, as the first coherent economic conception of an enterprise as a system, Professor Gutenberg's work provides a suitable frame of reference for assessing recent developments and putting them into perspective. When Professor Gutenberg wrote his seminal Grundlagen der Betriebswirtschaftslehre in the 1950s, his work was firmly rooted in the theory of the firm as it stood at the time. In the 1970s and 80s, this close relationship largely disappeared as a consequence of the profound changes which the microeconomic theory of the firm underwent under the influence of the new institutional economics. However, in the last few years, the pendulum has swung back. This is mainly due to the introduction of the new concept of complementarity into the theory of the firm...
urn:nbn:de:hebis:30-16688
Keywords: B25; L20; L22; 330; Complementarities; History of the Theory of the Firm; Incentive Systems; Organizational Theory; Theory of the Firm; Theorie der Unternehmung; Betriebswirtschaftslehre; Theorie